Trespassing a fusion of linguistic applications - Nisar, Mahvish; Nisar, Samia (International Multidisciplinary Research Journal, 2020)
This research paper aims to explore the cultural, political, and social realities of Pakistan in Uzma Aslam Khan’s novel Trespassing. The ethnic conflicts which engulfed Karachi in the 1990s in the aftermath of the Afghan War and Gulf War are also depicted. Mixed approach has been used as a tool in order to highlight different aspects of real life presented in the novel. These approaches are critical discourse analysis, punctuation as prosody of language, code mixing, and color semiotics. Code mixing in the novel gives a glaring picture of Pakistani culture and traditional values at the major level by the use of Urduised words. The application of critical discourse analysis in Trespassing reveals the political unrest, corruption, fantasy for America, individualism and ethnic conflicts which swamped the whole country. The prosody of punctuation illustrates the hidden meanings of the sentences more explicit thus making the societal issues more protuberant. The prosody is concerned with the semantic meaning rather than rhetorical meaning. Color semiotics of both eastern and western culture also objectified and presented a more comprehensive vision of the culture, ideas, and feelings in the novel. Trespassing is a book which is realistic and in all sense an essence of Pakistan and its people.